PENGARUH DIVIDEN PER SHARE (DPS), LABA BERSIH DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Melda Gusmirayanti; Adria Wuri Lastari; Efandri Agustian (JUMANJI (JURNAL MANAJEMEN JAMBI), 2023)
The purpose of this research is to analyze whether the dividend per share (DPS), net income and earning per share (EPS) affect the stock price on food an beverage industry in stock exchange on periode 2014-2018. This research is a desciptive quantitative research and analysis tool used in this research are simple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the purpose number 2 used statistical test F and test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free. The food and beverage sector is a sector where companies in Indonesia produce value- cadded products. Growth in this sector in Indonesia is supported by basic human needs for food and beverages, large populations, greater income and higher spending on high-rise middle-class food. Based on SPSS calculation results obtained F value count of 13,211 with a sig value of 0.043. This indicates that the value F count is greater than the value of the table F ((13,211 > 4,07) and the value is significantly smaller than the alpha value (0.043 < 0.05). Thus Ho was rejected and Ha was accepted. It means that DPR, net profit and EPS jointly influence the value of the company in food an beverage industry in stock exchange on periode 2014-2018. As for the advice that the authors can give in this research is as follows for the company should further increase the value of financial ratios that affect the increase in the stock price. For investors, can use the variable DPS, net profit and EPS together to see the feasibility of investing and investors can see from other variables that affect a partial to the stock price. For the development of science, this research can provide additional knowledge as a source of information and as a donation of thought in developing financial management disciplines. For further researchers we recommend using another ratio to calculate their impact on the share price as it can be possible another ratio also affects the increase in the company’s share price.